THE ADJUSTMENT OF EDUCATIONAL ADMINISTRATORS TO THE IMPACT OF INDUSTRIAL REVOLUTION 4.0 - Assoc. Prof. PhD. Tran Mai Uoc; Nguyen Long Giao (Galaxy International Interdisciplinary Research Journal, 2021)
Industrial revolution 4.0 is an indispensable trend of every country desiring to gain development, including Vietnam. Industrial revolution 4.0 has posed many problems that need to be solved in the education and training field, one of which is the competence development of educational administrators. The article analyzes issues related to the competence development of educational administrators in the context of industrial revolution 4.0, expressed through the contents related to required abilities of educational administrators, the basic shortcomings of educational administrators and the underlying causes, and policies to develop the competence of educational administrators.